Emotional Design in Concept Maps – No Support but Also No Burden - Lenski, Sina; Großschedl, Jörg (Frontiers in Education, 2022)
A concept map is a powerful learning method that promotes meaningful learning and is highly recommended for use in biology classes. According to multimedia research, the effectiveness of concept maps could be improved by the incorporation of pictorial elements. Apart from the use of realistic images, a new field of research claims that specific design manipulations, including human-like features with appealing colors (emotional design), influence learners’ affective state and thereby improve learning. Positive affective states are assumed to evoke emotions and provoke deeper cognitive processing, which increases the cognitive resources available for a task. We conducted two experiments with a total of N = 249 junior high school students, comparing the effect of learning material with emotional design illustrations (emotional design), with non-emotional design illustrations (neutral design) and without illustrations (control design). Experiment 1 examined the influence of these designs on students’ affective state, cognitive load (extraneous, intrinsic, and germane load), and learning performance (n = 202). By pre-post-test investigations, experiment 2 focused on whether the three different designs influence students’ affective state (n = 47). We found that emotional design led to a significant decrease of the perceived task difficulty but we did neither find an effect on learning performance nor on the affective state. Other than expected, the neutral design lead to reduced extraneous and intrinsic cognitive load but the emotional design did not affect the experienced cognitive load. Consequently, in terms of learning, emotional design in concept maps did not hamper learning but did not foster it either.